INFORMATION PERCEPTION ABOUT THE PREVENTION OF CORONAVIRUS 2019 EPIDEMIC OF PEOPLE IN BANGKOK - Watana, Chotima (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
This research article was to study information perception and problems about the prevention of the Coronavirus 2019 epidemic of People in Bangkok. The sample was people aged 18 years and over 400 people in Bangkok. No knowledge and experience of the Coronavirus 2019 is required. Using the purposive sampling method with non-probability and Purposive sampling. The instruments for data collection were 5-level rating scale questionnaires. which the validity was between 0.64-1.00 and the reliability was 0.69. and the data were analyzed by frequency, percentage, mean, and standard deviation. The result of the study showed that 1) Most people’s perception of the information on the holiday, use new media such as the Internet, websites, and social media, with the main purpose of up-to-date, content about the prevention of Coronavirus 2019. 2) Perception problems of the receiver is no time to follow up, perception problems of the content of unreliable information, perception problems of the print Media is no printed media to read because they do not subscribe or buy their own, perception problems of the broadcast radio is no radio to listen to. perception problems of the television is broadcast time. perception problems of the personal media is not having enough time / little time to meet, talk, give advice, and perception problems of the new media is false information, and fake news. Suggestions for improving the information perception such as there should be the disclosure of news information and Knowledge like the first round of the epidemic. should have an SMS alert. And should have data verification agency news information published by new media.